2015
DOI: 10.1007/s00405-015-3715-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of middle fossa plugging of superior semicircular canal dehiscences: clinically and instrumentally demonstrated efficiency in a retrospective series of 16 ears

Abstract: The objective of this study is to report the surgical outcome after middle fossa approach (MFA) plugging in patients suffering from a superior semi-circular canal dehiscence (SCD) syndrome. This is a retrospective case review. Tertiary referral center. Sixteen ears in 13 patients with a SCD syndrome suffering from severe and disabling vestibular symptoms with a bony dehiscence on CT scan >3 mm and decreased threshold of cervical vestibular evoked potentials (cVEMPs). We assessed preoperatively: clinical sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 40 publications
0
52
0
Order By: Relevance
“…25 Canal plugging procedures involve occlusion of the lumen of the canal. 1,6,7,[12][13][14][15][17][18][19][20][21][22]28 Most investigations suggest that canal plugging has a higher success rate than canal resurfacing 25 ; however, lack of consensus regarding a metric for operative success and inconsistent reporting of surgical complications preclude a strong recommendation regarding a single surgical technique at this time. 3 Regarding the present study, our results seem at least comparable to middle fossa canal plugging and superior to resurfacing or capping techniques for symptom control and low-frequency hearing improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Canal plugging procedures involve occlusion of the lumen of the canal. 1,6,7,[12][13][14][15][17][18][19][20][21][22]28 Most investigations suggest that canal plugging has a higher success rate than canal resurfacing 25 ; however, lack of consensus regarding a metric for operative success and inconsistent reporting of surgical complications preclude a strong recommendation regarding a single surgical technique at this time. 3 Regarding the present study, our results seem at least comparable to middle fossa canal plugging and superior to resurfacing or capping techniques for symptom control and low-frequency hearing improvement.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 Computed tomography (CT) imaging of the temporal bone identifies absent or thinned bone overlying the superior canal, and this area of decreased cochlear input impedance provides the basis for the ''thirdwindow hypothesis,'' in which clinical findings are explained by abnormal shunting of acoustic energy through the hypercompliant area of bony dehiscence. [8][9][10] Multiple clinical studies have demonstrated that surgical intervention can provide relief of clinical symptoms, 1,6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23] although no technique or approach has yet shown superior outcomes across the literature. [3][4][5]24,25 Studies continue to be limited based on the small sample size reported, making conclusions regarding operative technique difficult to assess.…”
mentioning
confidence: 99%
“…SNHL was reported in a minority of cases (3/16) (19). Another study did not report thresholds, but described a general improvement of AC with an average of 10 ± 23 dB HL (21).…”
Section: Resultsmentioning
confidence: 99%
“…Outcome measures included: the SRT (19), the Word Recognition Score (20), and the Speech Discrimination Score (13, 23). …”
Section: Resultsmentioning
confidence: 99%
“…The subgroup analysis of the case group did not reveal any statistically significant differences comparing bilateral to unilateral SCDS patients and patients who opted for surgery compared to patients who chose a conservative approach. Surgery has the potential to improve symptoms such as autophony, and pulsatile tinnitus ( 14 , 15 , 29 ). However, these symptoms are not measured by HUI, because it is a generic HRQoL instrument.…”
Section: Discussionmentioning
confidence: 99%